Effect of TACI Signaling on Humoral Immunity and Autoimmune Diseases - Yi Zhang; Jun Li; Ya-Min Zhang; Xiao-Ming Zhang; Juan Tao (Journal of Immunology Research)
Transmembrane activator and calcium-modulating cyclophilin ligand interactor (TACI) is one of the receptors of B cell activating factor of the tumor necrosis factor family (BAFF) and a proliferation-inducing ligand (APRIL). TACI is a regulator in the immune responses. TACI inhibits B cell expansion and promotes the differentiation and survival of plasma cells. The mechanisms underlying these effects probably involve changed expressions of some crucial molecules, such as B lymphocyte induced maturation protein-1 (Blimp-1) and inducible T-cell costimulator ligand (ICOSL) in B cells and/or plasma cells. However, abnormal TACI signaling may relate to autoimmune disorders. Common variable immune deficiency (CVID) patients with heterozygous mutations in TACI alleles increase susceptibility to autoimmune diseases. Taci−/− mice and BAFF transgenic mice both develop signs of human SLE. These findings that indicate inappropriate levels of TACI signaling may disrupt immune system balance, thereby promoting the development of autoimmune diseases. In this review, we summarize the basic characteristics of the TACI ligands BAFF and APRIL, and detail the research findings on the role of TACI in humoral immunity. We also discuss the possible mechanisms underlying the susceptibility of CVID patients with TACI mutations to autoimmune diseases and the role of TACI in the pathogenesis of SLE.